Substitutions of residues in a loop surrounding the active site of a P-I snake venom metalloproteinase abrogates its hemorrhagic activity - Camacho Umaña, Erika (2020)
Poster publicado en revista del congreso: 20th World Congress of the International Society on Toxinology